COMMON GRAMMATICAL ERRORS IN THE USE OF ENGLISH AS A FOREIGN LANGUAGE: A CASE IN STUDENTS’ UNDERGRADUATE THESES - Bambang Sugeng (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
This study aims to find out the multitude of students’ grammatical errors in their undergraduate theses and the learning materials needed to counter this problem. Thestudy was a survey involving 228 undergraduate theses from 28 English study programsfrom 17 out of the 34 provinces in Indonesia. Data analysis included grouping, counting,and ranking the data. The findings show that errors rank as follows: verb groups, finiteverbs, subject-verb concords, predicates, concords of nouns, concords of numbers, clauses,passive voice, and word choices. The common-core grammar materials, which containinter-lingual implications, are recommended to be used as a potential solution to improve the quality of undergraduate thesis writing for students of the English study program.Keywords: inter-language, grammatical errors, common-core grammar